Evaluation of the geotourism potential of selected geological sites in the eastern part of the borderland between the Siedlce Upland and Łuków Plain - Orłowska, Anna (Geotourism/Geoturystyka, 2018)
Evaluating the geotourism potential of geological objects is now one of the main directions of geotourism development in Poland. So far, these have been usually carried out for famous and interesting objects, which are situated in physical-geographical regions of great morphological-geological values and are places of high intensity tourism. However, recently more and more attempts have been made to evaluate geotourism potential of geological objects situated in the areas considered unattractive to tourists. This paper reports the results of such an attempt, which has been made in the eastern part of the borderland between two physical-geographical regions of low-intensity tourism, i.e. the Siedlce Upland and Łuków Plain. To evaluate the tourism potential of geological objects, the method of geosite evaluation has been used. The results allowed the author to distinguish the objects of high and unique scientifi c values, which may be proposed as geosites and a geotourist trails in the study area.//Ocena potencjału geoturystycznego obiektów geologicznych stanowi obecnie jeden z głównych kierunków rozwoju geoturystyki w Polsce. Dotychczas wykonywano ją najczęściej w przypadku znanych i ciekawych obiektów, znajdujących się w regionach fi zycznogeografi cznych o wysokich walorach morfologiczno-geologicznych, stanowiących miejsca charakteryzujące się intensywnym natężeniem ruchu turystycznego. Ostatnio jednak coraz częściej podejmowane są próby oceny potencjału geoturystycznego obiektów geologicznych, znajdujących się na obszarach uznawanych za mało atrakcyjne turystycznie. Taką próbę podjęto na obszarze pogranicza wschodniej części regionów fi zycznogeografi cznych Wysoczyzny Siedleckiej i Równiny Łukowskiej – regionów cechujących się mało intensywnym natężeniem ruchu turystycznego. Do oceny potencjału geoturystycznego wykorzystano metodę waloryzacji geostanowisk. Wyniki waloryzacji pozwoliły na wyróżnienie obiektów o wysokiej, naukowej wyjątkowości, stanowiącej podstawę do utworzenia geostanowisk oraz szlaku geoturystycznego na analizowanym obszarze.